2018
DOI: 10.2166/wst.2018.401
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of uninsulated and insulated hybrid anaerobic baffled reactor (HABR) operating at warm temperature

Abstract: In this research, a hybrid anaerobic baffled reactor (HABR) configuration was proposed consisting of a front sedimentation chamber and four regular baffled chambers followed by two floated filter media chambers for the treatment of domestic wastewater. Performance comparison of uninsulated and insulated HABRs was carried out operating at warm temperature (18.6–37.6 °C) under variable HRTs (30 h and 20 h). The study suggests that almost similar chemical oxygen demand (91% vs 88%), total suspended solids (90% vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…However, once HABR (I) recovered this situation and ran for an addition 100 d at 20 h HRT (except system idle for 42 days), higher PO 4 3- removal 50±22% was achieved by HABR (I) compare to 40±23% in HABR (U). It indicated that the insulation of HABR also increased PO 4 3- removal efficiency when operated for a longer time (140 d), which opposed to recent findings operating for a shorter time (e.g., 50 d)[45].…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…However, once HABR (I) recovered this situation and ran for an addition 100 d at 20 h HRT (except system idle for 42 days), higher PO 4 3- removal 50±22% was achieved by HABR (I) compare to 40±23% in HABR (U). It indicated that the insulation of HABR also increased PO 4 3- removal efficiency when operated for a longer time (140 d), which opposed to recent findings operating for a shorter time (e.g., 50 d)[45].…”
Section: Resultscontrasting
confidence: 64%
“…The average NH 4 + -N removal efficiency was 42±36% in HABR (U), and 47±42% in HABR (I). The recent study showed that the insulation of HABR increased NH 4 + -N removal by 7%[45], where the both HABRs were operated for 50 d (40 d for 30 h HRT, and 10 d for 20 h HRT). It was also observed that NH 4 + -N removal primarily occurred due to nitrification, which was observed high on day 18 and then gradually decreases afterward.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the average oxygen content increased from an average of 2 mg/L to 4 mg/L in inlet and outlet respectively. Khalekuzzaman and his co-worker also reported that dissolved oxygen was higher in the effluent [35]. This indicates oxic/anoxic conditions occur in ABR for organic biodegradation and nitrification/denitrification processes [29].…”
Section: Current Performance Of Abr Unitsmentioning
confidence: 99%
“…A key aspect influencing the AD process is the operating temperature (Khalekuzzaman et al 2018). Increasing or decreasing temperatures may affect the biological reaction rate or digestion performance within the ABR (Ali et al 2019;Chang et al 2020).…”
Section: Introductionmentioning
confidence: 99%